The Racial Ambiguities of American Sephardic and Ashkenazi Jews - Dayanim, Ezra (Iggrot Ha'Ari, 2023)
This paper analyzes the racial ambiguities of Sephardic and Ashkenazi Jews in American law by examining three Supreme Court cases: DeFunis v. Odegaard, Shaare Tefila Congregation v. Cobb, and Bennun v. Rutgers State University. Despite being classified as a religious group, Jews have also been subjected to racial categorization, with Sephardic and Ashkenazi Jews often occupying different racial spaces. Through a close reading of these cases, the paper explores how the Supreme Court has grappled with the complexity of Jewish identity in America, and how these cases have shaped the legal understanding of Jewishness as both a religious and a racial identity. Ultimately, the paper argues that these cases highlight the need for a more nuanced and inclusive approach to understanding race and ethnicity in American law, particularly in how it relates to the Jewish community.